2009
DOI: 10.1007/s11106-010-9170-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of holmium bismuthide

Abstract: presumably exists at temperatures below 541 K [1]. However, the paper [2] doubts whether it exists and proposes the refined phase diagram of this system ( Fig. 1), which is mainly based on the data reported in [1]. Holmium bismuthide HoBi melts congruently at 2048 ± 15 K and crystallizes in NaCl cubic syngony with lattice parameter a = 0.6226 nm [1]. The solid-state miscibility of holmium and bismuth is no more than 1 at.%.The thermodynamic properties of HoBi were examined with electromotive force (emf) measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…To weaken the interaction of holmium with the salt melt at elevated temperatures, we used a Ho-Bi alloy from the heterogeneity range [HoBi + (Bi)] as a reference electrode, whose thermodynamic properties we examined previously [22] in the range 673-873 K using emf measurement of the galvanic cell…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…To weaken the interaction of holmium with the salt melt at elevated temperatures, we used a Ho-Bi alloy from the heterogeneity range [HoBi + (Bi)] as a reference electrode, whose thermodynamic properties we examined previously [22] in the range 673-873 K using emf measurement of the galvanic cell…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…It is found that the values of activity of Ho in Ho-Bi alloys are in the order of 10 −13 to 10 −9 . Yamshchikov et al 43 and Antonchenko et al 44 determined the thermodynamic properties of HoBi intermetallics by emf measurements. It can be seen from Table II that our results are very close to the ones obtained by Yamshchikov et al 43 However, they are slightly larger than the values obtained by Antonchenko et al 44 The standard Gibbs free energies of formation for Ho-Bi intermetallics, HoBi and Ho 5 Bi 3 , are calculated by the equations presented in Table III.…”
Section: Open Circuit Chronopotentiometry-thermodynamic Formation Of ...mentioning
confidence: 99%